Tanggung Jawab Sosial Perusahaan dalam Islam - Ahdiyat Agus Susila (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2016)
Islam places great emphasis on the concept of responsibility, although it does not mean ignoring the organization and individual freedom. The concept of responsibility in Islam is essentially voluntary, without coercion. Responsibility of companies and employees in Islam, particularly on humans, because as social beings who could not let go of his interactions with other people in order to meet all their needs. Corporate social responsibility or Corporate Social Responsibility (hereinafter in this article will be abbreviated CSR) is a concept that organizations, especially (but not only) of the company is to have a responsibility towards customers, employees, shareholders, communities and the environment in all aspects of operations company. CSR is closely linked to “sustainable development”, in which there is an argument that a company in carrying out its activities must base their decision not solely based on financial factors such as profits or dividends but also must be based on social and environmental consequences for now and for the long term.